WHEAT GENOTYPES ASSESSMENT FOR SALINITY TOLERANCE USING MULTIVARIABLE SELECTION APPROACHES - S. M. Arain; M. Faheem; K. A. Laghari; M. A. Sial (Journal of Animal and Plant Sciences, 2023)
The salinity tolerance indices, principal component analysis, and cluster analysis were employed to evaluate the 16 wheat genotypes for agro-morphological traits under normal and saline (834-1850ppm/pH 7.3-7.5 soils) conditions for two consecutive years 2015 and 2016 at the Nuclear Institute of Agriculture (NIA), Tando Jam, Sindh, Pakistan. Combined analysis of variance revealed significant variations among the studied genotypes. Moreover, a significant interaction of genotype by year was observed only between grain yield and grains per spike indicated importance of the trait for improvement of grain yield in wheat. Correlation of Ys (yield under stress) and Yp (yield under non-stress) with tolerance index (TOL), stress stability index (SSI), yield stability index (YSI) and yield index (YI) indicated that mean productivity (MP), geometric mean productivity (GMP), harmonic mean (HM) and STI (stress tolerance index) were found as better indicators of Ys and Yp. The principal component analysis revealed two components that justified 73.23% of the total variation. Bi-plot and cluster analyses classified the genotypes i.e., V3-10-9, V3-10-31, and V3-10-32 based on MP, GMP, STI, and HM indices as stable and high yielding, while C3-98-8 and V2-10-15 based on YSI and YI. These genotypes could be exploited directly in the varietal release program and or as a source of potential donors to stack genes for salinity tolerance.
Keywords: Genotype by environment interactions; salinity tolerance; stress selection indices; principal component analysis; Bi-plot; cluster analysis; correlation; wheat